Example 2: The Italian law on compulsory vaccinations. (13th November 2019) - Signorelli, C
Abstract: In March 2017, the so-called "Lorenzin law" (named after former health minister Beatrice Lorenzin who was responsible for the bill) was introduced to implement compulsory vaccination for children six years old and younger to be allowed into the school system. Without proof of the required immunizations, including those for measles, mumps, rubella, chickenpox and polio, children were not eligible to attend kindergarten. But the Five Star Movement and the League, which formed a ruling coalition in 2018 to form the current government, pledged to scrap the vaccination obligation during the run-up to elections in March, courting the so-called "anti-vax" vote. The newly appointed minister of health, Giulia Grillo, adopted a temporary measure relaxing these vaccination requirements until the end of March 2019. The temporary measure allowed children to stay in school as long as their parents attested that the children had been vaccinated. A doctor's note was not needed. The temporary measure was adopted pending a complete revision of the law on compulsory vaccinations. As no new law was adopted in March 2019, the previous law returned to force, leading for instance to around 300 children in Bologna, Italy, not being admitted to kindergarten as they did not have the required immunizations. Amid confusion over the rules as the new school year begins, the governing Five Star Movement (M5S) presented parliament with an amendment that effectively halts its own reform and reinstates the previous vaccination requirements.